Magnetic Resonance Imaging-Based Prediction of the Relationship between Whiplash Injury and Temporomandibular Disorders - Lee, Yeon-Hee; Lee, Kyung Mi; Auh, Q-Schick; Hong, Jyung-Pyo (Frontiers in Neurology, 2018)
Abstract Purpose: Whiplash injury can cause internal derangement of the temporomandibular joint (TMJ) and lead to temporomandibular disorders (TMDs). Ouraim wasto evaluate whether the initial clinical findings in TMD patients with whiplash injury are correlated with their MRI characteristics. Materials and Methods: This case-control study involved 219 patients (135 women, 84 men; mean age: 37.84 years) who visited our orofacial pain clinic with TMD; TMD was diagnosed using the research diagnostic criteria for TMD Axis I. Patients were categorized into three groups based on the presence and type of macrotrauma: in the “wTMD” group, patients had suffered whiplash injury; patients in the “pTMD” group had post-traumatic TMD; the “iTMD” group comprised patients who had presented with TMD symptoms and had sustained no macrotrauma. We investigated the presence of disc displacement, effusion, disc deformity, and condylar degeneration, and changes in the lateral pterygoid muscle (LPM). To evaluate the severity of TMD pain and objectively analyze symptoms, we used a visual analogue scale (VAS), palpation index (PI), neck PI, dysfunction index (DI), and craniomandibular index (CMI). Results: The VAS scores, and the severity indexes of the TMD including PI, neck PI, and CMI were highest in the wTMD patients. Atrophy of the LPM was most commonly seen in the wTMD group, as was disc deformity. In wTMD patients only, VAS score was significantly correlated with stress; it was correlated with headache in wTMD and iTMD patients. The clinical symptoms of TMD were not correlated with MRI findings in the wTMD group. However, alterations in the LPM were strongly correlated with disc displacement. Conclusion: If clinicians recognize alterations in the LPM and disc displacement in the TMJ, they will better understand the clinical symptoms and pathophysiology of TMD with whiplash injury. Whiplash injury may lead to TMD via different mechanisms from other macrotraumas.